Application of Biotechnology in the Production of Derivatives of Dairy Products: A Review - Rahmawati Rahmawati; Larestananda Asmaul Husna Hizaumi Putri; Lutfiah Ayu Khoirunisa; Milenia Fitria Cholifah (Future Science, 2022)
The increasing population has led the food industry to be more adaptable in their business, especially in production aspects. This is due to the need for improving the quantity and quality aspects of end products, including dairy food products. To meet consumer expectations the food industries are urged to produce and/or modify the methods of production to ensure the quality of the food and production cost. This review focuses on the application of biotechnological aspects during the production of cheese, kefir, and yogurt, to obtain certain characteristics, especially its sensory attributes such as color, texture, taste, and odor.